SMS-based platform connecting farmers to Lawyers in Uganda - Mukasa, Hellen (Technical Centre for Agricultural and Rural Cooperation, 2019)
Hellen Mukasa, the co-Founder of Lawyers 4 Farmers shares how the SMS-based platform is connecting farmers in Uganda to Lawyers which saves them time and money.